CYCLOADDITION REACTIONS OF AZIDE, FURAN, AND PYRROLE UNITS WITH BENZYNES GENERATED BY THE HEXADEHYDRO-DIELS–ALDER (HDDA) REACTION - Chen, Junhua (2013)
Benzynes can be generated by the intramolecular thermal cycloisomerization of triynes–the title HDDA reaction. We report here that these can be trapped by cycloaddition reaction with trimethylsilyl azide (1,3-dipolar) or a furan or pyrrole (4+2 Diels–Alder).